Genotoxic effects of silver amalgam and composite restorations: Micronuclei-Based cohort and case-control study in oral exfoliated cells - S Jeslin Mary; K L Girish; T Isaac Joseph; Pradeesh Sathyan (Wolters Kluwer Medknow Publications, 2018)
Context: A huge number of people carry dental fillings which contain either mercury-based amalgam and/or the recently introduced methacrylate-based resins. It has been shown that both these materials are known to be leached into the oral cavity and induce genotoxic alterations in the buccal mucosal cells. Because of its low cost and ease of manipulation, dental amalgam is still widely used as a restorative material in developing countries. The health risks associated with the components of this restorative material has always been a matter of concern. The present study was designed to assess the frequency of micronuclei (MN) in oral mucosal cells as it is a promising tool for studying the genotoxic effect of clastogenic agents on them. Aims: The aim of this study is to evaluate the genotoxic effects of silver amalgam and composite restorations by measuring the mean number of MN in oral exfoliated cells. Materials and Methods: The present study was a prospective cohort study which includes a study group consisting of 110 participants. The study sample was equally divided into 55 participants requiring only amalgam restoration and 55 participants requiring only composite restoration in any permanent molar teeth. The same participants before the restoration formed the control group. Smears were obtained from each patient before and 10 days after restoration and were stained with DNA-specific Feulgen stain. The number of cells containing MN out of 500 cells were counted and recorded. After the evaluation of the slides, the results were compiled and subjected to statistical analysis. Results: There was a statistically significant (P < 0.01) variation in the mean number of MN after the restoration in both amalgam (5.41 ± 1.25) and composite (2.83 ± 0.85) restorations when compared to before the restoration. However, the mean number of MN in composite restoration was significantly less when compared to amalgam restoration. There was also a statistically significant difference in the mean number of MN in subjects with single restoration when compared with multiple restorations in both amalgam and composite restorations. Conclusions: The observations from the present study showed the genotoxic effect of amalgam and composite restorations on the oral cavity. However, composite restorations were least cytotoxic when compared to amalgam restoration. Future research and technical advancements are needed for developing safer materials for use in humans.